Cost-Effectiveness of Catheter Ablation Versus Antiarrhythmic Drug Therapy in Atrial Fibrillation: The CABANA Randomized Clinical Trial. Issue 7 (21st June 2022) - Chew, Derek S.; Li, Yanhong; Cowper, Patricia A.; Anstrom, Kevin J.; Piccini, Jonathan P.; Poole, Jeanne E.; Daniels, Melanie R.; Monahan, Kristi H.; Davidson-Ray, Linda; Bahnson, Tristram D.; Al-Khalidi, Hussein R.; Lee, Kerry L.; et al.
Abstract : Background: In the CABANA trial (Catheter Ablation vs Antiarrhythmic Drug Therapy for Atrial Fibrillation), catheter ablation did not significantly reduce the primary end point of death, disabling stroke, serious bleeding, or cardiac arrest compared with drug therapy by intention-to-treat, but did improve the quality of life and freedom from atrial fibrillation recurrence. In the heart failure subgroup, ablation improved both survival and quality of life. Cost-effectiveness was a prespecified CABANA secondary end point. Methods: Medical resource use data were collected for all CABANA patients (N=2204). Costs for hospital-based care were assigned using prospectively collected bills from US patients (n=1171); physician and medication costs were assigned using the Medicare Fee Schedule and National Average Drug Acquisition Costs, respectively. Extrapolated life expectancies were estimated using age-based survival models. Quality-of-life adjustments were based on EQ-5D–based utilities measured during the trial. The primary outcome was the incremental cost-effectiveness ratio, comparing ablation with drug therapy on the basis of intention-to-treat, and assessed from the US health care sector perspective. Results: Costs in the first 3 months averaged $20 794±SD 1069 higher with ablation compared with drug therapy. The cumulative within-trial 5-year cost difference was $19 245 (95% CI, $11 360–$27 170) and the lifetime mean cost difference was $15 516 (95% CI, –$2963 to $35, 512) higher with ablation than with drug therapy. The drug therapy arm accrued an average of 12.5 life-years (LYs) and 10.7 quality-adjusted life-years (QALYs). For the ablation arm, the corresponding estimates were 12.6 LYs and 11.0 QALYs. The incremental cost-effectiveness ratio was $57 893 per QALY gained, with 75% of bootstrap replications yielding an incremental cost-effectiveness ratio < $100 000 per QALY gained. With no quality-of-life/utility adjustments, the incremental cost-effectiveness ratio was $183 318 per LY gained. Conclusions: Catheter ablation of atrial fibrillation was economically attractive compared with drug therapy in the CABANA Trial overall at present benchmarks for health care value in the United States on the basis of projected incremental QALYs but not LYs alone.